Environmental gradients drive convergence in life history strategies among disparate but coevolved taxonomic groups - Carla L. Atkinson; Alex J. Franzen; Garrett W. Hopper; Jonathan W. Lopez; Zachery D. Zbinden; Caryn C. Vaughn (Ecology, 2025)
Trait‐based approaches can improve ecological understanding by linking fitness to the environment. The trilateral life history model is an expansion of r‐ and K‐selection theory that reflects trade‐offs between juvenile survival, fecundity, and generation time and describes differential survival of species across environmental gradients. We used this framework to generate and test hypotheses regarding community assembly and the validity of such a model in two disparate taxonomic groups, freshwater mussels and fish. We assessed the distribution of mussel and fish life history strategies across 80 sites spanning aspects of the river continuum concept within the Ouachita Highlands (USA) and asked if their distributions are predicted by a similar life history strategy framework. Because mussel and fish assemblages should both be structured by selective forces in an up‐ to downstream trajectory, we expected both taxa to converge on more species‐rich assemblages with a greater proportion of equilibrium strategists in larger, more stable downstream habitats. We found that both mussel and fish species richness increased with watershed area as well as the proportion of equilibrium strategists in the assemblages. Our study validates the use of the trilateral life history model to test hypotheses about the distribution patterns of two coevolved taxonomic groups.